1
$\begingroup$

The question to be solved is:

$$ \lim_{n \to \infty} \left( \ \sum_{k=10}^{n+9} \frac{2^{11(k-9)/n}}{\log_2 e^{n/11}} \ - \sum_{k=0}^{n-1} \frac{58}{\pi\sqrt{(n-k)(n+k)}} \ \right)$$

The first thing that occured to me was to transform the limits into definite integrals using the limit definition of integrals, so it'll become easier to evaluate.

However, I have no clue how to convert them into definite integrals. Could anyone please shed some light on how to proceed? Or is there a better way to solve this problem?

$\endgroup$
  • $\begingroup$ The first term is easy to compute. Just focus on the second as a Riemann sum. $\endgroup$ – Claude Leibovici Oct 2 '18 at 8:18
1
$\begingroup$

$$ \lim_{n \to \infty} \left( \ \sum_{k=10}^{n+9} \frac{2^{11(k-9)/n}}{\log_2 e^{n/11}} \ - \sum_{k=0}^{n-1} \frac{58}{\pi\sqrt{(n-k)(n+k)}} \ \right)$$

By putting $k=m+9$ in the first sum, we get \begin{align} \sum_{k=10}^{n+9} \frac{2^{11(k-9)/n}}{\log_2 e^{n/11}} &=\frac 1{\log_2 e^{n/11}}\sum_{m=1}^{n}(2^{11/n})^m\\ &=\frac 1{\log_2 e^{n/11}}\frac{(2^{11/n})^{n+1}-2^{11/n}}{2^{11/n}-1}\\ &=\frac{11\log(2)}{n}\frac{2^{11/n}(2^{11}-1)}{2^{11/n}-1}\\ &=\frac{11\log(2)}{n}\frac{2^{11/n}(2^{11}-1)}{e^{11/n\log(2)}-1}\\ &\sim\frac{11\log(2)}{n}\frac{2^{11}-1}{11/n\log(2)}\\ &\xrightarrow{n\to\infty}2^{11}-1 \end{align} For the second sum \begin{align} \sum_{k=0}^{n-1} \frac{58}{\pi\sqrt{(n-k)(n+k)}} &=\frac{58}\pi\sum_{k=0}^{n-1} \frac 1{\sqrt{1-(\frac kn)^2}}\frac 1n\\ &\xrightarrow{n\to\infty}\frac{58}\pi\int_0^1\frac{\mathrm dx}{\sqrt{1-x^2}}\\ &=\frac{58}\pi\frac\pi 2\\ &= 29 \end{align}

$\endgroup$
1
$\begingroup$

For converting an sum to definite integral :
Convert your sum having limits $a$ to $b$ to the form $f(k/n) * 1/n$. Take $k/n$ as $x$, $1/n$ as $dx$ and set the limits as $\frac{a}{n}$ and $\frac{b}{n}$. This is actually the sum of all tiny rectangles (vertical ones) when we break the area under a curve into small rectangles of width $\frac{1}{n}$.

For the first term, simplify the denominator and take $k-9=t$ . The first term becomes $2^{11\frac{t}{n}}$ $\frac{11\ln2}{n}$. You can now convert it to an Definite Integral and evaluate it. (It comes out to be $2^{11} - 2^0$). For the second term, take 'n' out of the denominator and convert it to an integral to get $29$. The answer comes out to be 'this year'.

$\endgroup$
1
$\begingroup$

The first summation is essentially a geometric series, and with $j:=k+9$,

$$\frac{2^{11(k-9)/n}}{\log_2 e^{n/11}}=\frac{\left(2^{11/n}\right)^j}{\dfrac{n}{11}\log_2e}.$$

Then summing from $1$ to $n$,

$$\frac{2^{11/n}(2^{11}-1)}{\dfrac n{11}\log_2e(2^{11/n}-1)}.$$

As

$$2^{11/n}-1=e^{11\ln2/n}-1=1+\frac{11\ln2}{ n}+\cdots-1,$$ the limit reduces to $2^{11}-1$.


As an integral, $$\frac{2^{11(k-9)/n}}{\log_2 e^{n/11}}\to 11\ln2\,2^{11x}dx$$ which integrates as $2^{11x}$, from $0$ to $1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.